TIPS DAN TRIK PENULISAN JURNAL DAN PUBLIKASI TERINDEKS SINTA 6 - Aisyah, Aisyah; Hayadi, B. Hermawan; Masriah, Masriah; Melati, Indah; Masruroh, Masruroh (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
Scientific publications are one of the important indicators in the development of science and academic quality in higher education. In Indonesia, the indexation of national journals is managed through the Science and Technology Index (SINTA) system which classifies journals based on their quality, one of which is SINTA 6-indexed journals. For students and novice researchers, publication in the SINTA 6 journal is often the first step in building an academic track record. However, many authors have difficulty writing scientific articles that meet the standards of journal publications. This study aims to examine various tips and tricks in writing journal articles and publication strategies in journals indexed by SINTA 6. The research method used is a literature study by analyzing various academic sources related to scientific writing and journal publications. The results of the study show that the success of scientific article publication is influenced by several main factors, namely the selection of relevant research topics, the preparation of a systematic article structure, the use of good academic language, and the proper management of references. In addition, the selection of journals that are in accordance with the scope of research and the author’s ability to respond to reviewers’ comments is also an important factor in the publication process. By understanding these various tips and tricks, the author is expected to be able to improve the quality of scientific articles and increase publication opportunities in SINTA 6 indexed journals.